2021
DOI: 10.1002/cam4.3722
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a prior malignancy on outcomes in gastric cancer patients

Abstract: Background The number of cancer survivors has increased rapidly, and there is a higher risk of developing a second cancer. Whether a prior malignancy could affect survival outcomes is unknown. We aimed to investigate the clinical characteristics and prognostic outcomes of prior malignancies in patients with gastric cancer. Methods Patient data were extracted from the Surveillance, Epidemiology, and End Results (SEER) database. We used the Kaplan–Meier method, competing risk models, and Cox regression models to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
(83 reference statements)
2
12
0
Order By: Relevance
“…First, we found that among the ICC patients with prior cancer, the prostate, breast, and colorectum were the top three most common sites. Similar results were also found in studies focused on other cancers [ 12 , 14 , 17 ]. This could be explained by the following reasons: (1) all three types of cancer have a high incidence, and in a recent study, breast, colorectal, and prostate cancer were reported to be the first, third, and fourth most commonly diagnosed malignancies worldwide, respectively [ 18 ]; (2) the indolent characteristics of the three types of cancer and the advancement in therapeutic strategies contribute to a prolonged OS for patients [ 19 21 ], and the relatively long-term survival time results in an increasing chance of developing a second malignancy.…”
Section: Discussionsupporting
confidence: 89%
“…First, we found that among the ICC patients with prior cancer, the prostate, breast, and colorectum were the top three most common sites. Similar results were also found in studies focused on other cancers [ 12 , 14 , 17 ]. This could be explained by the following reasons: (1) all three types of cancer have a high incidence, and in a recent study, breast, colorectal, and prostate cancer were reported to be the first, third, and fourth most commonly diagnosed malignancies worldwide, respectively [ 18 ]; (2) the indolent characteristics of the three types of cancer and the advancement in therapeutic strategies contribute to a prolonged OS for patients [ 19 21 ], and the relatively long-term survival time results in an increasing chance of developing a second malignancy.…”
Section: Discussionsupporting
confidence: 89%
“…, history of smoking and alcohol consumption) and SPCs’ characteristics ( e.g. , pathological features and treatment status); consequently, clinicians are unable to formulate an optimal treatment plan for the affected individuals ( Bian et al, 2021 ; Wen et al, 2021 ; Chen, Sun & Liu, 2022 ). In the present study, we comprehensively analyzed the clinical characteristics of DPCFGC patients and constructed a nomogram model based on the screened independent risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…However, because MPMNs with first GC have a sporadic clinical onset, published studies are mostly case reports; moreover, there is a lack of standardized international guidelines for the diagnosis and treatment of MPMNs with first GC; hence, clinicians have an insufficient understanding of the disease ( Miller et al, 2019 ; Vogt et al, 2017 ). Additionally, some studies that were based on American public databases could not accurately predict the prognosis of MPMNs patients owing to the exclusion of important information such as patients’ lifestyle and SPCs’ characteristics ( Chen, Sun & Liu, 2022 ; Wen et al, 2021 ; Bian et al, 2021 ). Therefore, in order to guide the clinical diagnosis and treatment of such patients, it is necessary to analyze their clinical characteristics and establish a comprehensive prognostic model.…”
Section: Introductionmentioning
confidence: 99%
“…The cohort was then established according to the following inclusion criteria: i) Patients diagnosed with FPM and SPM confirmed pathologically; ii) patients receiving at least one course of inpatient radio- or chemotherapy; iii) patients who developed SPM at an interval of ≥6 months, which is considered to be the standard for distinguishing between synchronous malignancy and SPM in the cohort of patients with breast or gastric cancer, the two main types of cancer that were separately analyzed in the present study ( 13 , 15 ); and iv) patients with regular follow up (recorded every ~2 months during the course of therapy, and at least every 3 months for 2 years, then every 6 months after the first 2 years).…”
Section: Methodsmentioning
confidence: 99%